ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT (Studi Empiris pada Perusahaan Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Hetty Sondang Gultom; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of the elements of the fraud diamond theory on fraudulent financial statements in companies listed on the Indonesia Stock Exchange (IDX). Fraudulent financial statement is an act intentionally carried out by management to present misleading financial information or information that does not reflect the actual condition.The independent variables used in this study include financial stability, external pressure, nature of industry, change in auditor, and change in director. The dependent variable used is fraudulent financial statement. The research objects consist of companies in the basic materials sector listed on the Indonesia Stock Exchange during the 2021–2023 period using purposive sampling method. The total research sample amounts to 165 company data. Secondary data were collected from financial statements and annual reports available on the IDX website and the official websites of the companies. The study employs logistic regression analysis to test the hypotheses.The results show that external pressure has a positive effect on fraudulent financial statements, while the other variables financial stability, nature of industry, change in auditor, and change in director are not proven to have an effect on fraudulent financial statements